Electromyographic activity of the upper limb muscle during specific salat’s position and exercise - Mohd Khairuddin, Mohd Safee; W. A. B., Wan Abas; F., Ibrahim; N. A., Abu Osman (2012)
This study investigated the muscle activity of the neck extensors (NE), sternocleidomastoideus (SCM) and biceps brachii (BB) muscles in healthy subjects during salat and specified exercises using surface electromyography (EMG). A group of undergraduates aged between 19 to 25 years voluntarily participated in this study. For the assessment of the NE and SCM, the subjects were asked to perform salat (salam’s position) and exercise [neck rotation exercise (NRE)]. Subjects were asked to perform takbir’s position and biceps dumbbell curl (BDC) to access BB. The EMG and the motion signals of the muscles were recorded. The findings indicate that there were contractions of the muscles during the salat and exercise with difference EMG level. For NE and SCM, Wilcoxon’s Rank Sum Test showed a statistically no significant difference between salat and exercise for NE (p = 0.482) and SCM (p=0.161). For the BB, Wilcoxon’s Rank Sum Test showed a statistically significant difference between salat and exercise (p<0.05) with differences 18.48% MVC. However, BB showed the EMG level with mild contraction. Therefore, salat may be useful in warm up exercise or in rehabilitation programs. This pilot study can be as initial research about other biomechanical response of human muscle with other position in salat.